Extension and Matching Grants for Improved Management: An Evaluation of the Uruguayan Livestock Program. (31st August 2015) - Mullally, Conner; Maffioli, Alessandro
Abstract : Offering matching grants along with extension services is a common tool of agricultural development policy and has the potential to address some of the shortcomings of purely private or public extension. Yet the evidence for the effectiveness of programs that combine extension with matching grants is quite thin. We add to this evidence by evaluating the Uruguayan Livestock Program (ULP), a program that promoted the adoption of intensive management practices by small and medium‐sized cattle producers by offering extension from private providers combined with matching grants for investments. Using inverse probability weighting as applied to an eight‐year panel data set of cattle producers, we find that the ULP had large impacts on net sales and production of calves, but that program impacts on production and sales translated into modest net economic impacts overall. We examine the mechanisms that may have driven ULP impacts, and conclude that program impacts were likely caused by improved management practices rather than by loosening liquidity constraints on producers.